Seroprevalence and Risk Factors of Contagious Bovine Pleuropneumonia in Selected Districts of North Gondar Zone, Ethiopia - Molla, Wassie; Jemberu, Wudu Temesgen; Mekonnen, Sefinew Alemu; Tuli, Getachew; Almaw, Gizat (Frontiers in Veterinary Science, 2021)
Contagious bovine pleuropneumonia (CBPP) is an infectious and highly contagious respiratory disease of cattle and water buffalo, which is caused by Mycoplasma mycoides subspecies mycoides small colony. It induces significant economic losses and lead to a serious food security and peoples’ livelihood problems in affected countries. The disease has been reported in different parts of Ethiopia with prevalence ranging from 1.78% to 96 %. However, there is not enough epidemiological information about CBPP in northwestern part of the country, particularly in North Gondar Administrative Zone. This cross sectional study, therefore, was conducted in four selected districts (Metema, Alefa, Quara and Dembia) of North Gondar Administrative Zone to estimate the seroprevalence of CBPP and to identify the potential predisposing factors for the spread and seropositivity of CBPP in the area. A total of 751 serum samples were collected from 41 herds (villages) having no history of CBPP vaccination. Information like age, sex, breed, herd size and management were collected during blood sample collection. Data related to agro-climatic zone, trade trekking (traveling on foot) route from or through CBPP endemic/epidemic zone, transhumance grazing route, vehicle route, and bordering with CBPP epidemic/endemic zone were obtained from district agricultural offices. The serum was screened for CBPP using competitive enzyme-linked immunosorbent assay (c-ELISA) test. The animal level and herd level apparent seroprevalences were 12.9% (95% CI: 10.7-15.5) and 65.9% (95% CI: 49.6-79.1), respectively. The true animal level and herd level prevalences were estimated at 20.1% (95% CI: 16.6-24.2) and 65.2% (95% CI: 48.6 -78.7%), respectively. At animal level, trekking route from or through CBPP endemic/epidemic zone to the study area (OR = 4.77 (95% CI: 1.92-11.84) compared to without trekking route) was identified as the most important risk factor for CBPP spread and seropositivity. In general, epidemiological evidence of the present study indicates that CBPP is a prevalent disease and animal trekking is important risk factor for spread of the disease in the study area and needs due attention from the government and other concerned bodies for its prevention and control to mitigate its economic impact.